Electrochemical Energy Storage Potentials of Waste Biomass: Oil Palm Leaf- and Palm Kernel Shell-Derived Activated Carbons - Salisu Nasir; Mohd Zobir Hussein; Zulkarnain Zainal; Nor Azah Yusof; Syazwan Afif Mohd Zobir (Energies, 2018)
In this study, activated carbons (ACs) were produced from oil palm leaves (OPL) and palm kernel shells (PKS) using different concentrations (0%, 11%, and 33%) of H3PO4 as the activating agent. The Brunauer⁻Emmett⁻Teller (BET) results indicated that surface area decreases with the decreasing of the concentration of the H3PO4 in the following order: AC from oil palm leaves was (OPLAC-0% H3PO4) < (OPLAC-11% H3PO4) < (OPLAC-33% H3PO4), with the BET surface area values of 37, 760, and 780 m2/g, respectively. Similarly, the PKS-derived AC followed the same trend of (PKSAC-0% H3PO4) < (PKSAC-11% H3PO4) < (PKSAC-33% H3PO4), with the BET surface area values of 3, 52, and 1324 m2/g, respectively. Based on this finding, it was observed that H3PO4 had exhibited an influential role on enhancing the surface properties of the AC. On the contrary, it slightly decreased the graphitic trait of the AC by considering their IG/ID trends, which were generated from the Raman spectral analysis. The energy storage capacity of the AC was further tested using cyclic voltammetry. Three of the samples were found to have high capacitance values of 434 F g−1, 162 F g−1, and 147 F g−1 at 5 mVs−1. The first (434 F g−1) is much higher than the specific capacitance value (343 F g−1) of the only oil palm leaf-derived porous carbon nanoparticles ever reported in the literature.